Relationship between nostalgia & motivation of football fans in Singapore towards intention to visit overseas stadium - Khoo, Er Chin (2019)
The European Football League is one of the popular sports by viewership worldwide. The purpose of this research is to identify the relationship between nostalgia, motivation and intention to visit. In specific, this study examines how nostalgia and motivation can affect intention to visit overseas stadium in the context of football. A total of 301 participants who needs to be a football fan, took part in this study through completing an online survey and 293 data were valid for analysis. Analysis of data was done through using software from Statistical Package for the Social Science (SPSS) to remove any outliers and Analysis of Moment Structures (AMOS) for the purpose of Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) testing. Results shows significant relationship between nostalgia and motivation (Hypothesis 1: 0.649, P < 0.001), motivation and intention to visit (Hypothesis 2: 0.857, P < 0.001) and an indirect significant relationship through motivation mediating nostalgia and intention to visit (Hypothesis 3: 0.556, P < 0.05). Results from this study suggests that nostalgia alone may not be able to influence first time visit intention unless with the mediating effect of fan motivation. Motivation encompasses the nostalgic feeling of football fans raising the urge and desire for sport tourism at football stadiums. Results from this study will enable tourism industry to understand the concept that both nostalgia and fan motivation are needed as a driving factor for football fans to visit overseas stadiums for the first time.